PRODUCTIVITY OF FISHERIES BAGAN FISHING BOAT AT BUNGUS OCEANIC FISHING PORT (PPS BUNGUS) WEST SUMATERA PROVINCE - Tamara, Rani; Brown, Arthur; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in April - May 2018 at the Samudera Bungus Fishery Port, West Sumatra Province. The purpose of this study is to (1) calculate the fishing productivity of bagan fishing seen from the productivity value of bagan fishing boat (2) find out the composition of the type of fish caught in the bagan fishing boat. One of the fleets that do a lot of fishing in the Ocean Bungus Fishery Port is one of them is boat charting equipment. Based on the 2018 ship logbook data, there are 111 boat vessels in the Ocean Fishing Port of Bungus. The number of bagan fishing boats that operate in the Ocean Bungus Fishery Port is ships with a size above 30 GT. So in this study 5 samples of the ship that were the majority were taken to calculate the productivity of the bagan fishing boat at Ocean Bungus Fishery Port. Bagan fishing productivity shows the boat productivity value of the bagan fishing for each ship is different based on the total catch (Kg) per effort to catch the number of daily catches where the highest productivity value is 16,58 Kg / minute in KM. Ikhwan Jaya - 02 on hauling the first day and the lowest productivity value was 0,61 Kg / minute in KM. Fadhil - 04 on hauling the first day. Composition of catches of each bagan fishing boat based on the time of withdrawal of the net (hauling) fluctuates. The composition of the type of fish on each bagan fishing boat during data collection is different. The kinds of fish caught were Cakalang (Katsuwonus pelamis), Layang (Decapterus russelli), Tongkol (Euthynnus affinis), Cumi – cumi (Loligo sp.), Teri (Stolephorus sp.), and Japuh (Dussumieria acuta) .Keywords :Bagan Fishing; Productivity; Composition; Bungus Oceanic Fishing Port